KOMPETENSI GURU PEMBIMBING KHUSUS DENGAN PENGAJARAN KOLABORATIF - Tita Rosita (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
Abstract The purpose of this study is to analyze the competence of special education teacher with collaborative teaching. The research method used is qualitative research that is literature study (library research). Based on the results of the literature study, it is found that collaborative teaching can develop the competence of Special Supervising Teachers in the area of specific abilities, namely the abilities needed to educate students of specific types of special needs. As for collaborative teaching, special education teacher can develop individual education programs that function as blueprints for special education programs.